2011
DOI: 10.1111/j.1365-2869.2011.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic limb movements in sleep are associated with stroke and cardiovascular risk factors in patients with renal failure

Abstract: SUMMARYPeriodic limb movements in sleep (PLMS) is prevalent among dialysed patients and is associated with increased risk of mortality. Our study aimed to determine the prevalence of this disease in a sample of transplanted and waiting-list haemodialysed patients. One hundred transplanted and 50 waiting-list patients underwent polysomnography. Moderate and severe diseases were defined as periodic limb movements in sleep index (PLMSI) higher than 15 and 25 events h )1 , respectively. The 10-year coronary heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…A higher prevalence of CVD has been shown in patients with PLMS in recent reviews [1,2,6]. However, current studies on the incidence of CVA between patients with and without PLMS have reported inconsistent results [7][8][9].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…A higher prevalence of CVD has been shown in patients with PLMS in recent reviews [1,2,6]. However, current studies on the incidence of CVA between patients with and without PLMS have reported inconsistent results [7][8][9].…”
Section: Introductionmentioning
confidence: 81%
“…Table 2). Therefore, 8 articles were eligible for the current meta-analysis (Table 1) [7][8][9][29][30][31][32][33].…”
Section: Study Selectionmentioning
confidence: 99%
“…111 Besides RLS, PLMS is also claimed to increase the risk of CVD in renal patients. In a study of kidney-transplanted patients and waiting-list subjects, Lindner et al 112 found that subjects with severe PLMS in either group, defined as PLMI >25/h, showed increased 10-year risk of coronary heart disease (by Framingham Score) compared with less severe PLMI (transplanted patients 18% vs 7%, P=0.002; waiting-list subjects 10% vs 4%, P=0.032). In the transplant group, severe PLMS also showed an increased 10-year risk of stroke (P=0.002).…”
Section: Secondary Rls/plms and Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…The cross-sectional design of this study precludes any directional or causal conclusions. 112 In another single hemodialysis center study, ESRD with PLMS (defined as PLMI ≥15/h) showed an increased risk of cardiovascular events (P=0.010) and mortality (P=0.008). Interestingly, the AHI and the oxygen desaturation index were not associated with mortality in this study, but the sample was small.…”
Section: Secondary Rls/plms and Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…The reduction in total sleep time caused by the syndrome and the association with the PLMs may suggest that an increase in sympathetic activity and even increased insulin resistance may occur in the long term. However, RLS is also more frequent in patients with renal, hepatic, neurological and reumatic diseases 36,37 , and may even increase cardiovascular risk in these patients 38,39 .…”
Section: Cardiovascular Consequencesmentioning
confidence: 99%